Similarities and differences - A comparison of International financial reporting Standards (IFRS) and Vietnamese GAAP - Pwc (https://www.pwc.com/, 2024)
First-time Adoption of International Financial Reporting Standards. Preparation Of Financial Statements. Revenue Recognition. Financial Instruments. Employee Benefits. Balance sheet and related notes. Investments. Other subjects.